Czynniki wpływające na decyzje producenta rolnego o wyborze środków ochrony roślin - Golinowska, Maria; Pytlarz-Kozicka, Maria (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
In 2006 research was carried out in Lower Silesia in purposely selected agricultural farms with an area from 50 to 200 ha. The purpose of the research was determining the factors influencing the agricultural producer's decisions concerning the choice of means of plant protection in the process of production. The research data were accumulated by means of the questionnaires, and worked upon by means of economical analysis. The research sample included 30 respondents. The qucstioned respondents were characterized by high agricultural quaIifications (60% with secondary or higher agricultural education). They can be described as young, as 76.6% were up to 50 years old. They ran the production activities on their own land (77%) and on rentcd land (23%). In thc analysed population only one producer rented 100% of land. The producers cultivated cereals in 74.1%, while rape constituted 13.9% of production. The process of production was financed mainly (in 80%) from their own means and got supported by bank loans or commodity loans. The respondents stated the following most important factors influencing the agricultural producers' decisions conccrning thc choice of means of plant protection: the price (86%), the possibiiity of negotiations (56.7%), the extensive service (43.3%), the rich assortment (20%), the convenient location (20%). (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 91-98